2004
DOI: 10.2169/internalmedicine.43.911
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardiac Mortality in Women Compared with Men in Patients with Acute Myocardial Infarction

Abstract: Objective It has been reported that women with acute myocardial infarction (AMI) have a higher short-term mortality rate than men, but the reason is not known. The profile in relation to age, gender and risk factors was evaluated to compare AMI and unstable angina pectoris (UAP).Methods Findings from 984 patients including 580 patients with AMI (129 women, 451 men) and 404 patients with UAP (131 women, 273 men) were analyzed by the South Osaka Acute Coronary Syndrome Study Group (SACS). The primary endpoint of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…In women, however, this pattern was not followed for all of the traditional risk factors. 11 Male ratio in MI for our study was lower than that reported by Kanamasa and colleagues, 8 but the downward trend in sex ratios between age groups was similar in Kanamasa and associates' study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In women, however, this pattern was not followed for all of the traditional risk factors. 11 Male ratio in MI for our study was lower than that reported by Kanamasa and colleagues, 8 but the downward trend in sex ratios between age groups was similar in Kanamasa and associates' study.…”
Section: Discussionsupporting
confidence: 71%
“…7 On the other hand, the women were older than men with MI, but the prevalence of DM and HTN was not different between the 2 sexes. 8 In another study, the prevalence of HTN and self-reported diabetes was very similar in men and women. Only 37% of the men exhibited none of the 3 risk factors, 39% exhibited 1 risk factor, and 24% had ≄2 risk factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparison of use ofĂą-blockers showed it was underused in females (63%) compared to males (75%) which is statistically significant (p=0.046).This finding is consistent with previous reports. 9,10,[12][13][14][15] The significant underuse of Ăą-blockers in female patients in our study may be explained by the fact that more females had diabetes mellitus and congestive heart failure. International data support the fact that despite recommendations in favour of use of Ăą-blockers, these are still underused in post-infarct patients, at the expense of many lives lost 17 .…”
Section: Discussionmentioning
confidence: 69%
“…Similar results were also reported by others. 9,10,12 Regarding treatment with reperfusion, in our series, we used Streptokinase for reperfusion therapy within 12 hours of symptom onset in cases of eligible STEMI patients. Streptokinase was significantly underused in females (15.6%) compared to males (32.2%) (p=0.011).Underuse of reperfusion therapy was also reported in other studies.…”
Section: Discussionmentioning
confidence: 99%